Quantitative Proteomic Analysis Indicates That Pggt1b Deficiency Promotes Cytokine Secretion in Resiquimod‐Stimulated Bone Marrow‐Derived Macrophages via the NF‐κB Pathway - Shanshan Yu; Xuecui Wei; Fangyuan Long; Heng Gu; Zhimin Hao (Immunity, Inflammation and Disease)
ABSTRACT Background Psoriasis is a systemic inflammatory skin disease mediated by the innate and adaptive immune systems. Recent studies have indicated that macrophages may contribute to the pathogenesis of psoriasis. However, the role of macrophage protein geranylgeranyl transferase type‐1β subunit (PGGT1B) in psoriasis is unclear. In this study, we aimed to establish how a reduction in Pggt1b expression in monocytes influences the onset and progression of psoriasis. Methods Myeloid cell‐specific Pggt1b knockout mice were generated, and their bone marrow‐derived macrophages (BMDMs) were stimulated with resiquimod (R848) to mimic the psoriatic immune microenvironment. The proteomic analysis enabled us to identify 17 differentially expressed proteins associated with Pggt1b deficiency in the psoriasis macrophage model (folded change ≥ 1.3 and p < 0.05). Gene Ontology and Kyoto Encyclopedia of Genes and Genomes enrichment was performed. Quantitative reverse transcription‐polymerase chain reaction (qRT‐PCR) and western blot assays were used to verify the differentially expressed proteins and signaling pathways. Finally, an enzyme‐linked immunosorbent assay was used to verify the expression of the key inflammatory cytokine interleukin (IL)‐1β. Results In total, six proteins (Dlgap5, Fas, Fnta, Nlrp3, Cd14, and Ticam2) were identified as hub proteins. Furthermore, we found that Pggt1b might mediate R848‐induced inflammation via the small G‐proteins Rac1 or Cdc42. We found that Pggt1b positively regulates pro‐inflammatory responses in R848‐stimulated BMDMs via the NF‐κB signaling pathway. Conclusions This study clarified that PGGT1B affected the synthesis of inflammatory cytokines via NF‐κB pathway and provided insights into the mechanisms underlying immune responses and inflammation.